Satisfaction levels of elite taekwondo players in Turkey - Ramazanoglu, F. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The job satisfaction which depends on subjective decisions is expressed as the satisfaction or positive feelings that the person feel after making self-discussions about the person's job. The sportsmen are in sports with their feelings, thougts and merits along with their physical being. It is possible to express the satisfaction in sports as the attitude of the sportsman to sports. The aim of this research is determining the level of the satisfactory of the elite taekwondo players in Turkey, and helping to the improvements in that way. Methods The research has been made among 88 male and 23 female elite taekwondo players, who had won degrees at national championships in Turkey. And also a survey adapted from the short form of ''Minnessota Satisfaction Questionnaire (MSQ)'' has been made among these players. The classification shows the rate of satisfaction, very low between 20-39 points, low between 40-59 points, enough btween 60-79 points, high between 80-100 points. The data were evaluated by the SPSS program. With respect to the survey frequency analysis, satisfaction average and satisfaction point were calculated. According to the income amount and working period variables, the t-test; according to the education level and working perods variables; the k2 tests were applied. Results According to the income amount, age group, educational level and the working period variables in the t-test results there were produced a meaningful relation about a rank p<0,05. According to the k2 test which was evaluated about the education level and working period, the rank was found p<0,05. Discussion / Conclusion At he result of the research it is seen that, the only part that the players are not satisfied is the fee. Elite taekwondo players answered to the question about fee satisfaction in survey in negative way (SP=37,47) and showed their low satisfaction about their fees. According to the job satisfaction, the players showed high satisfaction at the survey, in their answers about the job they are having (SP=81,90). In the end of the survey, it has been clearly determined that the general satisfaction state is high and the only topic that the state shows they are not pleased about is the fee.